AN ANALYSIS OF CONVERSATIONAL IMPLICATURE STRATEGY IN A DRAMA â€œTHE BEARâ€ BY ANTON CHEKHOVAND ITS APPLICATION IN ELT - Suryadi, Hendra; Muslim, Muslim (UNDIKMA Mataram (Eks. IKIP Mataram), 2019)
This study was aimed at finding analysis of conversational implicature in a drama ?the bear? by Anton Chekhov and its application in English language teaching